Insecticidal Activities of Abroma Augusta (L.) Chloroform and Methanol Extracts Against Tribolium Castaneum (Herbst) Adults - Mondal, Omar Ali; Haque, Esarul; Haque, Jahurul; Khan, Ataur Rahman (Journal of Life and Earth Science, 2014)
The chloroform and methanol extracts of the leaves, root wood, stem bark, stem wood and seeds of Abroma augusta (L.) (Ulatkambal) were tested against Tribolium castaneum (Herbst) adults through residual film assay. The seed extracts (CHcl3 and MeOH) were found to offer the highest mortality of the beetles and the LD50 values were 3046.083, 247.9217 and 75.96001 ?g/cm2 and 6598.793, 340.4855 and 113.6461 ?g/cm2 for the (CHCl350 values of 1127.785, 312.5822 and 146.3708 ?g/cm2 and 1689.468, 449.8259 and 134.9692 ?g/cm2 for the (CHCl3350 values of 3466.807, 450.3049 and 175.7438 ?g/cm2 and 4654.238, 1010.538 and 333.7202 ?g/cm2 for the(CHCl3350 values of 3295.859, 1137.558 and 363.1539 ?g/cm2 and 3717.851, 566.2215 and 230.7044 ?g/cm2 for the (CHCl33A. augusta did not show any activity against the beetles. According to the intensity of activity observed through mortality of the adult beetles the potentiality of the chloroform extracts could be arranged in a descending order of seeds> root wood > leaf> stem bark and for the methanol extracts, seed>root wood > stem bark > leaf. DOI: http://dx.doi.org/10.3329/jles.v8i0.20134 J. Life Earth Sci., Vol. 8: 11-15, 2013